Analyses and pollution potential of heavy metals at the Jerangau-Jabor landfill in Kuantan, Malaysia - How, Fiona Ni Foong; Mohd Noh, N.S; Nordin, N. A; Abang Sapani, D. F. N (University of Tehran, 2020)
The impact of Industrialization has always been related to the better economic and social transformation. However, it should be well planned for environmental sustainability. Landfilling is the most used municipal solid waste (MSW) disposal method in Malaysia. Raw and treated leachate collected from Jerangau-Jabor Landfill Site (JJLS), Kuantan, Pahang were analysed for the content of silver, cadmium, chromium, copper, iron, lead, zinc using Flame Atomic Absorption Spectrometry (FAAS) and Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The metal analyses result were compared with standard limits from the Environmental Quality (Control of Pollution from Solid Waste Transfer Station and Landfill) Regulations 2009, Malaysian Environmental Quality Act 1974 (Act 127) set by the Department of Environment, Ministry of Natural Resources and Environment, Malaysia and used to calculate the sub-leachate pollution index of heavy metals (sub-LPIhm) to evaluate the pollution potential of the heavy metals. The sub-LPIhm is one of the sub-index needed to calculate the Leachate Pollution Index (LPI) together with the sub-LPI organic (sub-LPIorg) and sub-LPI inorganic (sub-LPIinorg). LPI is the level of leachate pollution potential of a landfill site. All the heavy metals in the raw leachate were significantly higher than the treated leachate. Some were found to be above the permissible standard limit stipulated in the regulation. However, the sub-LPIhm showed that the level of heavy metal pollution potential of the leachate is low. It is recommended that the treated leachate should undergo continuous treatment to ensure the discharge leachate complied with the standard limit.